Utilizing DNA barcoding approach to study the diversity of the blue swimming crab from Tuban District, East Java, Indonesia - MARITA IKA JOESIDAWATI; NINING NURSALIM; NENIK KHOLILAH; EKA MAYA KURNIASIH; NI KADEK DITA CAHYANI; AMBARIYANTO AMBARIYANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Joesidawati MI, Nursalim N, Kholilah N, Kurniasih EM, Cahyani NKD, Ambariyanto A. 2023. Utilizing DNA barcoding approach to study the diversity of the blue swimming crab from Tuban District, East Java, Indonesia. Biodiversitas 24: 4731-4737. Blue swimming crabs are one of the economically significant fisheries resources in Indonesia. However, Indonesia's blue swimming crab fisheries still depend on wild catches that lead to a non-target species harvest, especially the cryptic swimming crabs. This study aims to investigate the genetic diversity of blue swimming crab specimens and other cryptic species using a molecular approach (DNA Barcoding). The samples were caught from the waters of Tuban District, East Java, Indonesia, using traditional foldable traps or "bubu lipat". This study utilized the Polymerase Chain Reaction (PCR) method targeting the Cytochrome c Oxidase Subunit I (COI) gene. The sequences were then compared to the NCBI database to get the closest species based on the sequences. 21 out of 23 samples were identified as Portunus pelagicus, and two samples were identified as Charybdis feriata with percentage of similarity ranging from 99.68% to 100%. The phylogenetic trees were constructed using Neighbor Joining and Maximum Likelihood method with sequences from Scylla serrataas an outgroup. The genetic distance between P. pelagicus and C. feriata was 16%, whereas the genetic distance between P. pelagicus and C. feriata to the outgroup was 20%. The molecular method is crucial for species identification and population stock assessment. This information helps in determining stock boundaries, estimating population sizes, and understanding the genetic health of populations. Genetic data will help the government to have a better management of the fisheries activities in Indonesia by providing the diversity and population data.